Peningkatan Hasil Belajar Pak BP Melalui Discovery Learning Fase C Kelas 5 UPTD SD Negeri 076716 Lolohia Nias Barat - Masalumi Waruwu; Hartutik Hartutik; Paulus Asriadi (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The results of observations regarding student creativity in teaching and learning activities at UPTD SD Negeri 076716 Lolohia Nias Barat, especially in the subjects of Catholic Religious Education and Character Education, are very lacking, as well as learning outcomes that have not reached the predetermined target, only 55% have completed the KKM. The aim of this research is to improve creative and cognitive aspects by applying the Discovery Learning phase C learning method for class 5 UPTD SD Negeri 076716 Lolohia Nias Barat. This Classroom Action Research (PTK) consists of 4 stages, namely, planning, implementation, evaluation, reflection and 2 cycles. The research subjects were 6 Class 5 Face C students. Obtaining data: 1) observation with indicators of observing the creative aspect of the Pancasila Student Profile (P3): generating original ideas, clarifying statements, asking many questions, seeing things from different perspectives, applying ideas according to the context and coming up with various alternative solutions, and 2) material learning outcomes test with achievement targets of 40% proficient, 40% proficient, 20 adequate, 0% just developing. The research results showed: There was an increase in the creative aspect of P3 from cycle 1, an average of 55.6% with the developing category, cycle 2 with an average of 91.00% in the very developing category. In terms of learning achievement, there has been an increase in the number of achievement targets from proficient 40% to 60%, proficient 40% to 40%. Suggestion: in the process of teaching and learning activities, teachers should apply a variety of learning methods and plan one dimension of the Pancasila Student Profile.